The Use of Aqidah Akhlaq Textbook to Increase Learning Outcome - Very Khoirotul Hakimah; Dian Kusuma Wardani; Hilyah Ashoumi (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This research begins with a problem regarding: 1. The development of the use of textbooks in the subject of aqidah akhlaq. 2. The development of student learning outcomes in the subject of aqidah akhlaq. 3. Knowing how much influence textbooks have on the subject of aqidah akhlaq. The research was conducted by a teacher so that in carrying out the task of educating, teaching and guiding students to achieve the desired goals and how the impact of using textbooks on improving student learning outcomes can affect student interest in learning. The population in this study were students of VII-K class at MTsN 3 Jombang. The sample in this study was taken from 20 students of class VII-K. As for the data analysis used the t test (paired), after the t test (paired) showed that the significant value was 0,031 > 0,05, so the average student learning outcomes had an effect on the use of aqidah akhlaq textbooks on student learning outcomes. Applying textbooks effectively improves student learning outcomes.